A CANAVALE e o setor sucroalcooleiro no Vale do São Lourenço : o associativismo rural e suas perspectivas frente ao desenvolvimento socioambiental - Martins, Joelmir Nunes (2017)
Reconciling economic development with socio-environmental sustainability is the challenge of the productive sector. The sugar and alcohol sector has its current industrial bias as a synonym for industry that modernizes and transforms the raw material into products important for consumption, however, this activity can generate negative social and environmental impacts. The objective of the present work is the analysis of the cooperation of the canavieiro rural associativism for the socioenvironmental development of the São Lourenço Valley through the trajectory of the sugarcane suppliers' association of the São Lourenço Valley - CANAVALE. For this purpose, specific information was presented on this relationship, in order to analyze the socioeconomic and socioenvironmental influences of this association in the region of the São Lourenço Valley and the sustainable development of the chain. The work adopted the method of exploratory-qualitative research, to verify the bottlenecks within this chain and the aspects related to the degradation of natural resources of the region, caused by the manufacturing process, since the socio-environmental through industrialization is affected by socioeconomics And macroeconomics imposed by the capitalist system, as well as the impacts generated by the industrial monopoly exerted on the region's economy. In order to achieve the proposed objective, the records that marked the trajectory of CANAVALE's productive process and action were observed through documents, official documents, minutes and testimonies, interviews were carried out with actors who participated in the process of Institution, as well as workers who participated actively in the associative activity. The consequences of the industrial and technological incision through state or private credits from National Development Programs without the planning, starting from the first of the own knowledge, generated the bankruptcy of the industry, the economic fragility of the producers and suppliers of sugarcane, As well as the weakness of the association through the challenges of the market, service to local socioeconomics and conscious use of natural resources.